Jawabanmu

Jawaban paling cerdas!
2014-05-29T16:02:59+07:00
F(x) = x⁴ + 4x³ + ax² + bx - 12 habis dibagi (x² + x - 6) = (x+3)(x-2)
f(-3) = (-3)^4 + 4(-3)³ + a(-3)² + b(-3) - 12 = 0
     ⇔ 81 - 108 + 9a - 3b - 12 = 0
     ⇔ 9a - 3b = 39
     ⇔ 3a - b = 13 .......................................(1)

f(2) = 2^4 + 4.2³ + 2²a + 2b - 12 = 0
     ⇔ 16 + 32 + 4a + 2b - 12 = 0
     ⇔ 4a + 2b = -36
     ⇔ 2a + b = - 18 ...................................(2)
Eliminasikan pers(1) dan (2)
3a - b = 13
2a + b = -18 +
5a        = -5
a = -1 substitusikan ke salah satu persamaan
2a + b = - 18 ⇒ -2 + b = -18 ⇒ b = -18 + 2 ⇒ b = -16

2 5 2